2006
DOI: 10.1038/nature04786
|View full text |Cite|
|
Sign up to set email alerts
|

Titan Radar Mapper observations from Cassini's T3 fly-by

Abstract: Cassini's Titan Radar Mapper imaged the surface of Saturn's moon Titan on its February 2005 fly-by (denoted T3), collecting high-resolution synthetic-aperture radar and larger-scale radiometry and scatterometry data. These data provide the first definitive identification of impact craters on the surface of Titan, networks of fluvial channels and surficial dark streaks that may be longitudinal dunes. Here we describe this great diversity of landforms. We conclude that much of the surface thus far imaged by rada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 12 publications
3
79
0
Order By: Relevance
“…Observations of the high abundance of methane in its nitrogen atmosphere led to suspicion that there might be a surface-atmosphere methane cycle similar to Earth's water cycle (Owen, 1982;Atreya et al, 2006). New evidence, particularly from Cassini, demonstrates this is truer than was expected with observations providing evidence for wind processes (Radebaugh et al, 2008;Lorenz et al, 2006), continuing erosion Barnes et al, 2007b;Elachi et al, 2006), clouds (Brown et al, 2002;Griffith et al, 1998), and even apparent liquid bodies (Stofan et al, 2007). Changes due to an active methane cycle (Turtle et al, 2009) and possible recent cryovolcanic activity (Lopes et al, 2007;Wall et al, 2009) further strengthens the Earth-like parallels.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of the high abundance of methane in its nitrogen atmosphere led to suspicion that there might be a surface-atmosphere methane cycle similar to Earth's water cycle (Owen, 1982;Atreya et al, 2006). New evidence, particularly from Cassini, demonstrates this is truer than was expected with observations providing evidence for wind processes (Radebaugh et al, 2008;Lorenz et al, 2006), continuing erosion Barnes et al, 2007b;Elachi et al, 2006), clouds (Brown et al, 2002;Griffith et al, 1998), and even apparent liquid bodies (Stofan et al, 2007). Changes due to an active methane cycle (Turtle et al, 2009) and possible recent cryovolcanic activity (Lopes et al, 2007;Wall et al, 2009) further strengthens the Earth-like parallels.…”
Section: Introductionmentioning
confidence: 99%
“…Soderblom et al, 2007a) and radar on the morphology (e.g. Elachi et al, 2006). Some notable geomorphic features are shown in Figure 5.7.…”
Section: Titan: Methane-based Aridity?mentioning
confidence: 97%
“…However, the discovery of large linear dune fields was one of the first major discoveries of the Cassini mission (Elachi et al, 2006). Although no ventifacts are visible in the Huygens descent images, the presence of dunes and the implications of abundant sand and at least episodically strong winds implies that, at least locally, wind may be a major process in rock disintegration.…”
Section: Aeolian Landformsmentioning
confidence: 99%
“…RADAR observations in February 2005 (flyby T3), found many radar-dark subparallel features, nicknamed 'cat scratches' which were interpreted (Elachi et al 2006) as being possibly aeolian in origin, although it was impossible to preclude other processes (Fig. 13).…”
Section: Aeolian Features On Titanmentioning
confidence: 99%
“…Cassini-Huygens has revealed Titan's surface in much greater detail, although the compositions of the materials responsible for Titan's albedo variations are complex and still not fully understood even after several years of Cassini observations . Nonetheless, morphologic interpretations of observations by Cassini's ISS, VIMS, and RADAR experiments and by Huygens' Descent Imaging Spectral Radiometer (DISR), have confirmed that darker regions consist of accumulations of liquid and solid hydrocarbons (e.g., Porco et al 2005b;Elachi et al , 2006Tomasko et al 2005;Lorenz et al 2006a;Barnes et al 2007a;). …”
Section: Titan Lakes and Seasmentioning
confidence: 99%